Mekanisme Perkembangan Sistem Saraf pada Tahap Organogenesis Awal - Puput Fuji Aslamiah; Pundy Vidiapuri; Astuti Kusumorini (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
The development of the nervous system is a crucial process during early organogenesis that impacts overall body function. This research aims to understand the mechanisms involved in the formation of the nervous system, focusing on early embryonic development. Previous studies indicate that interactions between genetic and environmental factors significantly influence this development, yet many specific aspects remain to be explored. This study provides an in-depth analysis of the role of progenitor cells and molecular signals in neuron differentiation. By identifying the pathways involved, it aims to uncover new approaches to understanding developmental disorders of the nervous system. Utilizing experimental methods and systematic data analysis, this research not only enhances our understanding of the fundamental mechanisms of nervous system development but also opens possibilities for developing therapies for related disorders